Genetic polymorphisms and expression of HLA‐G and its receptors, KIR2DL4 and LILRB1, in non‐small cell lung cancer. Issue 6 (9th April 2015) - Wiśniewski, A.; Kowal, A.; Wyrodek, E.; Nowak, I.; Majorczyk, E.; Wagner, M.; Pawlak‐Adamska, E.; Jankowska, R.; Ślesak, B.; Frydecka, I.; Kuśnierczyk, P.
Abstract Human leukocyte antigen‐G (HLA‐G) is a nonclassical HLA class I molecule absent from most normal tissues but detected in many malignant tumors. It is recognized by cells of the immune system using LILRB1, KIR2DL4 and LILRB2 receptors. We attempted to find out whether some polymorphisms of HLA‐G, LILRB1 and KIR2DL4 genes are associated with susceptibility to nonsmall cell lung cancer (NSCLC). Four polymorphisms in HLA‐G, i.e. −964A>G (rs1632947), −725C>G>T (rs1233334), −716T>G (rs2249863) in the promoter, and a 14 base pair insertion/deletion (14 bp indel) in the 3′‐untranslated region (3′UTR), and five in LILRB1 – 5651G>A (rs41308748) in intron 14, 5717C>T L622L (rs1061684), 5724G>A E625K (rs16985478), 5774 C>A P641P (rs41548213) in exon 15, and 5806C>T (rs8101240) in 3′UTR – as well as 9620 9A/10A (rs11410751) polymorphism in exon 7 of KIR2DL4 were typed using different laboratory techniques. Only one single nucleotide polymorphism (SNP) in HLA‐G (‐964A>G) and one in LILRB1 (5724G>A) were found to influence the risk of NSCLC. In addition, 5724G>A was associated with protection from tumor cell infiltration of regional lymph nodes. Most importantly, we detected HLA‐G and LILRB1 expression in tumor specimens, but no correlation with genetic polymorphisms was observed. HLA‐G and LILRB1 protein expression levels in tumor tissue were significantly correlated with tumor stage.